EVALUATION OF GRADUATE PROGRAMS IN BRAZIL: THE CASE OF THE FEDERAL UNIVERSITY OF RONDÔNIA (UNIR) - Souza, Lucas da Silva (Seven Editora, 2025)
The study analyzed the stricto sensu graduate programs of the Federal University of Rondônia (UNIR), considering institutional offerings and the scores assigned by CAPES between 2017 and 2020. The research sought to answer the following question: What are the active stricto sensu graduate programs offered by the Federal University of Rondônia (UNIR), and how have these programs been evaluated by CAPES during the 2017–2020 period? A qualitative approach was adopted, with a descriptive character and basic nature, grounded in bibliographic and documentary procedures. The deductive method was employed to interpret institutional data and official reports. The results indicated the existence of 31 stricto sensu graduate programs, with scores ranging from 3 to 5, including UNIR’s own courses and those in partnership with associated institutions. It was observed that the university plays a crucial role in expanding higher education within the state, although there is a concentration of programs, especially doctoral ones, on the Porto Velho campus. CAPES evaluations revealed satisfactory ratings, demonstrating the institution’s commitment to academic quality. Inter-institutional partnerships emerge as important strategies to expand offerings and integrate knowledge; however, challenges remain regarding decentralization, researcher retention, and incentives for applied research. DOI: https://doi.org/10.56238/sevened2025.038-011